Prayer, civic engagement and culture: A comparative study of Serbia and Malta - Pulis, Matthew; Ćumura , Ljiljana; Buhagiar, Luke (Sociološki pregled, 2024)
Contemporary open societies are characterised by pluralism, indicating differences in values and practices. Religiosity and civic engagement are intertwined in various ways, with processes changing across the Balkans and Southern Europe. Accordingly, in this study, we present the results of a survey that explores different relationships between (a) socio-demographic variables, (b) types of prayer engaged in by people, and (c) civic engagement in Serbia (the Balkans) and Malta (Southern Europe). Questionnaires with the same content were distributed in Malta (in English) and in Serbia (in Serbian). Our analysis reveals both similarities and differences relating to the following two main patterns: (1) all types of prayer correlated significantly with civic engagement behaviour in both countries; and (2) the frequency of prayer types, and the correlations between specific prayer types and civic engagement behaviour, ranked differently in both countries. Our discussion focuses on the implications of these patterns for open societies and intercultural dialogue.